Índices parasitarios en peces de consumo humano de piscigranjas del eje carretero Iquitos-Nauta 2023 - Rodríguez Chu, Luciano Alfredo (2023)
Fishes of fish farming importance in the Peruvian Amazon such as Arapaima gigas, Osteoglosom bicirrhossum, Colossoma macropomum, Piaractus brachypomus, Prochilodus nigricans, Brycon amazonicus, Myloplus schomburgkii and Pseudoplatustoma punctifer are parasitized by protozoan and metazoan parasites with different levels of infection/parasitic infestation. Given the importance of fish farming of species for human consumption in the Amazon and the possible parasitic conditions, the main objective of this study was to know the level of parasitism through the calculation of parasitological indices in native fish species of the Peruvian Amazon. The objective was to identify the parasite species, characterize them morphologically and get information for recognizing the characteristic symptoms of each identified parasite. In the present study, samples of fish species acquired from fish farming centers and a commercial aquarium on the Iquitos-Nauta highway were analyzed. Samples were analyzed in the Laboratory of Parasitology and Aquaculture Health of the Peruvian Amazon Research Institute (IIAP) in Loreto, Peru. Analysis of the fish revealed the presence of Dawestrema cycloancistrum on A. gigas, Trichodina sp. at high levels of infestation, Eustrongylides sp. in O. bicirrhossum, Psinoodinium sp. in high parasitic indices, as well as the monogenoids Anacanthorus spatulathus, Notozothecium januachensis, Mymarothecium boegeri, M. iiapensis, Diplostomum sp, Austrodiplostomum compactum and Procamallanus (Spirocamallanus) inopinatus in C. macropomum; A. penilabiatus and M. viatorum in P. brachypomus; Tereancistrum curimba in P. nigricans; Jainus amazonensis in B. amazonicus; A. camposbacae, A. carmenrosae, N. nanayensis and N. bethae in M. schomburgkii and the branchiuran Dolops discoidalis in P. punctifer. The highest parasite indices were registered in the protozoa Psinoodinium sp. and Trichodina sp. Regarding the parasitic metazoans, D. cycloancistrum was the one that registered the highest parasitic indices. The results of the study lead to the conclusion that the level of infestation/parasitic infection depends on the fish and the parasitic species, however, prophylactic and control measures must be adopted in order to guarantee the health of the fish and consequent success in the captive breeding of these fish species in the Peruvian Amazon.